NURSING INTERVENTION APPLICATION OF WARM COMPRESS TO INCREASE BREAST MILK PRODUCTION: A RAPID EVIDENCE REVIEW - Mamuroh, Lilis; Marcelline, Ericha; Kosim, Kosim; Sukmawati, Sukmawati (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2026)
Breast milk is the best source of nutrition for infants aged 0–24 months because it contains nutrients, antibodies, and enzymes that are essential for growth and immunity. The WHO and UNICEF recommend exclusive breastfeeding for the first six months because it has been proven to improve infant development and protect against disease. However, many mothers experience obstacles such as delayed production and blocked milk ducts. One effective non-pharmacological solution is warm compresses, which work by increasing blood flow and the release of prolactin and oxytocin hormones, therapy facilitating milk production and secretion. This literature review aims to examine the effectiveness of warm compresses on milk production in postpartum mothers. The method used was a scoping review guided by the PRISMA Extension for. Scoping Review, using the PICO search strategy. Literature searches were conducted through the Pubmed, EBSCO, ScienceDirect, and Scopus databases, as well as a manual search on Google Scholar for the period 2021-2025.the results of the study showed that interventions to facilitate breast milk massage and warm compresses, traditional Thailand massage, steamed ginger extract, with warm compresses, warm compresses for breast milk stagnation, warm compresses for smooth breast milk flow, warm compresses for breast production, warm compresses for reducing breast milk stagnation. From the selection results, seven relevant articles were obtained. The application of warm compresses to the breasts of postpartum mothers has been proven to be an effective, safe, and easy-to-implement non-pharmacological nursing intervention in increasing milk production and facilitating milk flow in postpartum mothers. It hoped that future researchers can conduct further research on interventions or other methods to increase breast milk production.